A prototype for project management game development using high level architecture. (1st January 2014) - Ekyalimpa, Ronald; AbouRizk, Simaan M.; Mohamed, Yasser; Saba, Farzaneh
Construction games teach students various concepts of managing project risks, making critical resource allocation and utilisation decisions, activity sequencing and other related construction issues. Past game development environments range from programs running monolithically on standalone computers to synthetic environments that support distributed modules (programs) running concurrently on different computers. This paper discusses one such environment, the construction synthetic environment (COSYE) based on high level architecture (HLA), which has potential as a game development environment. Then a framework for developing project management games within COSYE is proposed, based on experiences from previous game developments. Examples of games discussed include the bidding game, a tunnelling game and a crane lift planning game. This framework is meant to simplify game development. The paper highlights specifications for an administrator, a player and a simulator module.